S-E-R-V-E a theoretical framework for Christian leadership - Karl Inge Tangen (Scandinavian Journal for Leadership & Theology, 2024)
This article introduces a new perspective on Christian leadership. The theoretical framework critically integrates and transforms Gary Yukl’s theory of four meta-categories of leadership. It is argued that spiritual leadership should be defined as a distinct meta-category. Spiritual leadership includes self-transcendent practical wisdom (phronesis), occurring Coram Deo. This serves as the integrating center of the model. Furthermore, change-oriented leadership is reconceptualized as visionary leadership grounded in the Christian story. Yukl’s basic description of relational behavior is expanded through the lens of Christian virtue ethics. Effective leadership is understood as stewardship, requiring a balance between internal moral goods and external instrumental goods. The church’s external relations are defined in terms of missional or evangelistic hospitality. Consequently, Christian leadership comprises five key dimensions: spiritual, effective, relational, visionary leadership, and external relations, summarized in the acronym S-E-R-V-E.